Pelatihan Kepemimpinan Bagi Pengurus OSIS dan ROHIS SMP, SMA dan SMK Nusantara Ciputat - Hajar, Elvira Sitna; Saefullah, Aep; Fadli, Ahmad; Fahri, Fahri; Kohar, Abdul; Siregar, Fuad; Jayaun, Jayaun; Wicaksono, Adi; Tafsiruddin, M.; Saksana, Joned Ceilendra; Arda, Devid Putra; Tjiwijdjaja, Halim; Kusnaedi, Ujang; Candra, Hendra; Zulkarnain, Nizar; Rombouw, Sahrul; Paokuma, Hasbibi (LPPM STIE Ganesha, 2024)
This community service activity aims to enhance leadership skills among students of SMP, SMA, and SMK Nusantara. The objectives of this activity include equipping participants with basic leadership skills applicable to school organizations, encouraging the development of responsible, integrity-based, and inspirational leadership characters, facilitating the exchange of ideas on leadership, and increasing participants' motivation to actively engage in organizational and community activities The activity was held on Saturday, June 29, 2024, from 08:00 to 12:30 WIB, in Auditorium R. 86-87 of SMA Nusantara, Jl Tarumanegara Dalam No 2, Kelurahan Pisangan, Kecamatan Ciputat Timur, Kota Tangerang Selatan. Participants included OSIS and Rohis board members from four schools, namely SMP Nusantara Plus, SMA Nusantara Plus, SMK Nusantara 1, and SMK Nusantara II Kesehatan, with a total of 80 students. The implementation methods included seminars for material presentation, interactive discussions, and leadership practice simulations. The results showed high levels of active participation and enthusiasm from the participants, indicating that the activity successfully enhanced their leadership capacities. This positive impact is expected to continue encouraging students' self-development and active roles in advancing their school and community environments